Five Sesquiterpenoids from a Marine-Derived Fungus Aspergillus sp. Isolated from a Gorgonian Dichotella gemmacea - Wei, Mei-Yan (Molecular Diversity Preservation International, 2010)
Three new phenolic bisabolane-type sesquiterpenoids: (+)-methyl sydowate (1), 7-deoxy-7,14-didehydrosydonic acid (2), and 7-deoxy-7,8-didehydrosydonic acid (3), together with two known fungal metabolites were isolated from the fermentation broth of a marine-derived fungus Aspergillus sp., which was isolated in turn from a gorgonian Dichotella gemmacea collected from the South China Sea. Their structures were elucidated by combined spectroscopic methods, and the structure of 1 was further confirmed by single-crystal X-ray data.